(untitled) (Research, Society and Development, 2021)
The scenario of social distancing caused by the COVID 19 pandemic imposed a reorganization in the teaching-learning process. The teachers had to reinvent themselves, since most did not have the necessary skills to work in remote education and the students, who studied in person, had to adapt to the new reality and consequently overcome the challenges imposed. In this context, the professors realized the importance of interdisciplinary collaborative work and active methodologies. This article aims to analyze the impacts that the actions of the interdisciplinary project "Projects and production: challenges in the midst of the pandemic of COVID-19", carried out during the pandemic of Covid-19, in the period from May to June 2020, caused in the teaching-learning process of a class of the Technical Course in Administration Subsequent to High School, face-to-face modality, face-to-face mode , of the Federal Institute of Rondônia. The methodological mobilization occurred through a qualitative approach, of an applied nature, based on the bibliographic research and the description of the data and facts observed, in addition to the field research, using the questionnaire as an instrument. We identified some positive impacts on the students’ school performance, due to the participation in the project, where it was possible to observe a motivation during and at the end of the proposal, in addition to the feedbacks and perceptions pointed out by the students. Therefore, it is perceived the need to encourage the culture of new actions that can boost the teaching process, mobilizing unique learning experiences related to the realities experienced by academics, enabling the propagation of an education that transforms realities, and drives students to a life of success.